USE OF COMBAT SIMULATION TOOLS IN THE PROCESS OF TRAINING OFFICERS OF THE NATIONAL GUARD OF UKRAINE - Iokhov, Oleksandr; Lavrinchuk , Oleksandr; Horielyshev, Stanislav (Honor and Law, 2023)
The main problematic issues in the training of officers of the tactical and operational levels of the National Guard of Ukraine (NGU) are the lack of a sense of the dynamics of the development of events in real time when performing the tasks of the CPX training, which reduces the quality of coordination of the headquarters (military management bodies) of the NGU; lack of functional compatibility between NGU and military formations of NATO member countries for the training of military management personnel. A promising way to improve the process of officer training is the use of means of simulating combat operations, on the basis of which it is necessary to conduct practical classes and CPX training, as well as various activities within the framework of international cooperation. The article deals with the training of officers of the tactical and operational level and the conduct of military training of units of the NGU with the use of means of simulating combat operations. Reasoned purpose, structure and main tasks of the simulation modeling center of NSU as part of the National Academy of the NGU. The simulation modeling center of NGU will consist of two research departments and a department of software and technical support and maintenance. In addition, the structure and tasks of the stationary and mobile components of the simulation modeling center of NSU are given. The center's specialized software is based on the JCATS simulation system. The JCATS simulation system is a multi-functional, interactive, multi-level system used by the military and other government organizations as a tool for training, analysis, research, planning and practice for a variety of tasks. The capabilities of the JCATS simulation modeling system and the concept of conducting CPX training in accordance with the specifics of the service and combat activities of units and parts of the NGU were considered. Conducting exercises using combat simulation tools is aimed at practicing the practical skills of commanding troops in a constantly changing environment. Modeling is possible at the level of an individual soldier to NGU brigades. The proposed proposals for the creation and implementation of means of simulating combat operations will allow solving both educational tasks related to the training of tactical and operational level officers, as well as scientific and research tasks.